Evaluating the surface properties of HA coating on Co-Cr based alloy substrate - Kheimeh Sari, Hirbod Maleki (2014)
Hydroxyapatite (HA) is the main structural component of natural bone and due to its excellent biocompatibility and bioactivity it can be used in biomedical application as a coating layer for metallic implants to help formation of chemical bonding at HA/bone interface and work as a protective layer against ion release from a metallic prosthesis. In this study, HA bioactive coating was created using sol-gel method on the high carbon CoCrMo substrate. Although sol-gel is simple and cost effective method with capability to control chemical composition and able to coat on the complex-shape implants, massive cracks of HA sol-gel coated layer on implants are still the major issue. Cracks can be minimized by changing the viscosity, composition or variation in heat treatment procedure. In this study, Na3PO4 and CaCl2 were used as the main precursors in sol-gel preparation. The sol-gel was centrifuged at three different speeds (1500, 1750 and 2000 rpm). Coated specimens were sintered at 500°C, 600°C and 700°C for 20 minutes and 1 hour respectively. HA coated samples were analyzed under FESEM, XRD, AFM and electrochemical corrosion tests. The initial FESEM test revealed that the best centrifuging speed that results in a crack free HA coated layer at room temperature is 1750 rpm with viscosity of 1798 CP. The FESEM and XRD results also revealed that the best surface morphology with semi-crystalline microstructure belong to the sample sintered at 600°C for 20 min. Also it is concluded that sintering temperature above 600°C for HA coating on Co-Cr based alloys results in cracks propagation. Moreover, in terms of surface roughness all coated and sintered samples except the one sintered at 500°C for 20 min, showed a good result as well. Finally, in terms of corrosion resistance the sample sintered at 600°C for 20 min showed the corrosion rate almost 3.5 times lesser than uncoated sample.